Comprehensive systematic review: evaluating association of various movement screening tools with injury prediction in soccer athletes - Singh, A.; Singh, A. (Trends in Sport Sciences, 2024)
Introduction. Movement screening is used in soccer to evaluate an injury risk and create training regimens to prevent sports injuries. Movement screening has become popular in soccer, but there are some doubts about its accuracy. This systematic review was conducted to determine evidence supporting a relationship between various movement screening instruments and injury prediction in soccer players. Methods. The databases MEDLINE, CINAHL, Scopus, EMBASE, and SPORTDiscus were searched. Movement screening tests were used to evaluate athletes in prospective cohort studies. Musculoskeletal injuries were a primary outcome. Results. An analysis, including 14 studies with the following indicators, was conducted: diagnostic precision, relative risk, or odds ratios. There is strong evidence that some subcomponents of the Functional Movement Screening, Y Balance Test, Single Leg Drop Jump, Single Leg Countermovement Jump, and Landing Error Scoring System can predict common soccer injuries. Conclusions. The results suggest that screening tests can be incorporated into physical examinations to identify soccer players susceptible to an injury risk. Therefore, movement screening should be recommended as an injury prediction tool in soccer.